In Vitro and In Vivo Prebiotic Activities of Purified Oligosaccharides Derived from Various Local Bananas (Musa sp.): Tanduk, Uli, Raja Sereh, and Cavendish (Indonesian Society for microbiology, 2017)
To evaluate the activity of purified oligosaccharides (POS) as prebiotic from various different local bananas (Musa sp.); Tanduk (T), Uli (U), Raja Sereh (RS), and Cavendish (C); and to investigate their capacity in promoting the growth of Lactobacillus sp., in vivo. In vitro investigation: Oligosaccharides from various different local bananas were purified by 80% ethanol extraction. Subsequently, absolute ethanol was reconstituted before precipitation/centrifugation for glucose removal. Water was also removed by freeze drying. POS from the four bananas were analyzed by Thin Layer Chromatography (TLC). Prebiotic activity of POS was investigated by measurement of Prebiotic Activity Score (PAS).In vivo investigation: Balb/c mice were grouped into 6 groups with different prebiotics supplementation: negative control (4 mice, standard feed), positive control (6 mice, 15 mg of inulin/g/day), and samples (5 mice, 150 mg of T, U, RS, or C banana/g/day) for 40 days. Following 40 days after treatment, fecal viable counts of Lactobacillus sp. and Enterobacteriaceae of Balb/c mice was measured (CFU/g) and analysed. PAS value revealed a positive correlation between the oligosaccharides from bananas and Lactobacillus paracasei, with PAS value for T (0.05), RS (0.15), U (0.33) and C (0.77). Overall data suggest that fecal viable counts of Lactobacillus sp. increased after 25 days administration of U, RS, and C banana when compared to controls. Contrastingly, the fecal viable counts of Enterobacteriaceae decreased after 40 days administration of U, RS, and C banana compared to the control. Different types of local bananas demonstrate diverse prebiotic activities: U and C promote Lactobacillus sp. growth and reduce Enterobacteriaceae count. PAS value of U and C suggest potential prebiotic activity, whereas T and RS do not.